Liens entre les pratiques enseignantes perçues au collégial, le SEP à réussir ses études et le stress des étudiants - Christine Pelletier; Éric Frenette; Nancy Gaudreau (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Rates of psychological distress in students pursuing postsecondary studies are increasing. This problem is present in Quebec’s cegeps (Gosselin et Ducharme, 2017), and is mostly studied from a clinical perspective with the goal of providing specialized services to students (Baik et al., 2019). This article poses the following question: What can teachers do to develop self-efficacy in students and decrease their stress level? Better knowledge about teaching practices that are likely to develop students’ self-efficacy to succeed in their studies could provide some answers to this question. This study, based on a quantitative and exploratory approach, focuses on links between teaching practices in college, self-efficacy to succeed in one’s study, stress and participants’ sociodemographic data (n = 355). The following results are discussed: 1) relations between sociodemographic data (gender, age, program) and perceived teaching practices, 2) relations between four types of teaching practices and self-efficacy to succeed in one’s studies, 3) negative relation between self-efficacy to succeed in one’s study and stress, 4) relations between stress and teachers’ use of fear appeals and participants’ gender and 5) indirect effect of self-efficacy on efficacy appeals and stress, and positive relations and stress.